Real-world characteristics of patients with severe asthma prior to starting dupilumab: the ProVENT study - Korn, Stephanie; Schmidt, Olaf; Timmermann, Hartmut; Watz, Henrik; Gappa, Monika; Radwan, Amr; De Prado Gomez, Lucia; Atenhan, Anne; Bărbuş, Sebastian Liviu; Thakur, Mayank; Lommatzsch, Marek (Respiration, 2024)
Introduction: Dupilumab is approved for the treatment of severe type 2 (T2) asthma; however, the characteristics of patients receiving dupilumab in routine clinical practice are incompletely understood. This study describes the characteristics of patients with severe asthma before dupilumab treatment in a real-world setting. Methods: This interim analysis of an ongoing real-life study of dupilumab assessed baseline characteristics of the first patient cohort enrolled in the ProVENT study. Results: A total of 99 patients (59% females) were analyzed (17% received another biologic before dupilumab treatment and 15% were on maintenance oral corticosteroid treatment). Adult-onset asthma (>18 years) and an allergic phenotype were documented in 58% and 48% of patients, respectively. Median (interquartile range) age was 54 (40-61) years; the median number of exacerbations in the last 24 months was 1 (0-3); median fractional exhaled nitric oxide (FeNO) value was 38 (23-64) ppb; and median blood eosinophils (bEOS) count was 184 (8-505) cells/mu L. According to the United Kingdom Severe Asthma Registry classification, 53% of patients had T2 intermediate asthma (bEOS >= 150 cells/mu L or FeNO >= 25 ppb), 17% had T2 high asthma (bEOS >= 150 cells/mu L and FeNO >= 25 ppb), and 4% had T2 low asthma (bEOS <150 cells/mu L and FeNO <25 ppb). At least one GINA criterion for T2 airway inflammation was documented in 70% of patients. T2 comorbidities were observed in 64% of patients. Conclusions: This analysis suggests that patients eligible for dupilumab treatment display various clinical and biochemical characteristics rather than one clear-cut phenotype.
Gesehen am 22.04.2024
Online verfügbar: 12 Dezember 2023